2020
DOI: 10.1002/ejoc.202000298
|View full text |Cite
|
Sign up to set email alerts
|

Site‐Specific N2‐dG DNA Adducts: Formation, Synthesis, and TLS Polymerase‐Mediated Bypass

Abstract: The N2‐position of deoxyguanosine (dG) in DNA is susceptible to modification by various damaging agents. These modifications (lesions or adducts) can stall the DNA replication by replicative polymerases, and if the common DNA repair pathways do not remove them, it can result in genomic instability. This generally leads to the death or oncogenic transformation of the cell. An important mechanism to deal with this problem is Translesion synthesis (TLS), a bypass mechanism, which involves the tolerance of DNA dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 172 publications
(192 reference statements)
0
6
0
Order By: Relevance
“…In this work, several N 2 -adducts of guanine were studied with PrimPol: N 2 -Et-dG, N 2 -Ib-dG, N 2 -Bn-dG, N 2 -Naph-dG, N 2 -Anth-dG, N 2 -Pyre-dG, and LG (Figure ). The formation and synthesis of these DNA adducts have been discussed previously. , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this work, several N 2 -adducts of guanine were studied with PrimPol: N 2 -Et-dG, N 2 -Ib-dG, N 2 -Bn-dG, N 2 -Naph-dG, N 2 -Anth-dG, N 2 -Pyre-dG, and LG (Figure ). The formation and synthesis of these DNA adducts have been discussed previously. , …”
Section: Resultsmentioning
confidence: 99%
“…The formation and synthesis of these DNA adducts have been discussed previously. 23,47 To evaluate the ability of human PrimPol to synthesize past N 2 -dG adducts, primer extension reactions in the presence of Mg 2+ (10 mM) or Mn 2+ (1 mM) ions and 400 nM PrimPol were carried out. In the running start assay, PrimPol incorporated dNMPs opposite N 2 -ethyl-dG (+5 position upstream of the primer) but could not extend DNA synthesis beyond the lesion in Mg 2+ -reactions (Figure 2, lane 3).…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to endogenous and exogenous genotoxic agents can lead to the formation of various DNA lesions, many of which block replicative DNA polymerases and require TLS polymerases for their replicative bypass . A large body of literature revealed the roles of B- and Y-family polymerases in modulating the cytotoxic and mutagenic properties of various DNA lesions. , In this vein, Pol IV and Pol V were found to participate in error-free TLS and induce a −1 frameshift mutation at the site of an N 2 -dG adduct of benzo­[ a ]­pyrene; Pol II, however, is involved in bypassing the bulky N 2 -dG adduct of acetylaminofluorene and elicits a −2 frameshift mutation at the lesion site. , In addition, previous in vitro biochemical studies showed that purified Pol IV preferentially inserts a dCMP opposite N 2 -Et-dG, N 2 - i Bu-dG, and N 2 -CE-dG in template DNA, , though the kinetic parameters for nucleotide insertions opposite simple N 2 -alkyl-dG lesions were not measured. It will be important to determine, in the future, the efficiencies and fidelities of Pol II- and Pol IV-catalyzed nucleotide incorporation opposite the N 2 -alkyl-dG lesions.…”
mentioning
confidence: 99%
“…18,19 In this vein, Pol IV and Pol V were found to participate in error-free TLS and induce a −1 frameshift mutation at the site of an N 2 -dG adduct of benzo[a]pyrene; Pol II, however, is involved in bypassing the bulky N 2 -dG adduct of acetylaminofluorene and elicits a −2 frameshift mutation at the lesion site. 20,21 In addition, previous in vitro biochemical studies showed that purified Pol IV preferentially inserts a dCMP opposite N 2 -Et-dG, N 2 -iBu-dG, and N 2 -CE-dG in template DNA, 11,22 though the kinetic parameters for nucleotide insertions opposite simple N 2 -alkyl-dG lesions were not measured. It will be important to determine, in the future, the efficiencies and fidelities of Pol II-and Pol IV-catalyzed nucleotide incorporation opposite the N 2 -alkyl-dG lesions.…”
mentioning
confidence: 99%